Conservative Approach in An Intra-Articular PIPJoint Fracture Dislocation: A Clinical Case Report - Dholu, Dr. Urva; Solunke, Dr. Swaroop; Deshmukh, Dr. Ashwin; Patil, Dr. Amit (International Journal of Basic and Applied Sciences, 2025)
We report the case of a 25-year-old male who sustained an intra-articular fracture-dislocation of the ‎proximal interphalangeal (PIP) joint of the ring finger during a cricket match. Despite being advised ‎of surgical fixation, the patient opted for non-operative management. The fracture was treated using ‎a dorsal extension block splint combined with early rehabilitation. Follow-up radiographs and ‎clinical assessments demonstrated excellent joint stability, pain resolution, and full restoration of ‎function. This case illustrates the viability of conservative treatment in select cases of PIP joint ‎injuries, emphasizing appropriate fracture reduction, early mobilization, and a structured ‎rehabilitation protocol‎.